A Mehrotra Type Predictor-Corrector Interior-Point Method for P∗(κ)-HLCP. (10th October 2022) - Hazzam, Nadia; Kebbiche, Zakia
Abstract: In this article, a new variant of Mehrotra type-predictor-corrector algorithm is proposed for P ∗ ( κ ) -horizontal linear complementarity problem. We demonstrate the theoretical efficiency of this algorithm by showing its polynomial complexity. The iteration bound is given by O ( n A ( 1 + 4 κ ) ( 2 + 4 κ ) Γ log ⁡ 1 ϵ ) . We test the practical efficiency and the validity of our algorithm by running some computational tests.